Taking Berlin : the bloody race to defeat the Third Reich - Dugard, Martin (Dutton Caliber, an imprint of Penguin Random House LLC, 2022)
"A nonfiction thriller about the race between the Allies and Soviets to conquer the heart of Nazi Germany"--